2002
DOI: 10.1212/01.wnl.0000037480.59194.85
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide-induced neuropathy

Abstract: Thalidomide induces a dose-dependent sensorimotor length-dependent axonal neuropathy; it should be judiciously used with close neurologic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(100 citation statements)
references
References 27 publications
3
96
0
1
Order By: Relevance
“…8 It is increasingly recognized that BIPN may be a proteasome inhibitor class effect and that autoimmune factors and inflammation may also trigger BIPN. 2,3,9,10 To our knowledge, only one full paper published to date describes neurophysiologic and pathologic findings after bortezomib administration in animal models. 11 In this study, spinal cord was morphologically normal.…”
Section: Pathogenesis Of Peripheral Neuropathymentioning
confidence: 99%
“…8 It is increasingly recognized that BIPN may be a proteasome inhibitor class effect and that autoimmune factors and inflammation may also trigger BIPN. 2,3,9,10 To our knowledge, only one full paper published to date describes neurophysiologic and pathologic findings after bortezomib administration in animal models. 11 In this study, spinal cord was morphologically normal.…”
Section: Pathogenesis Of Peripheral Neuropathymentioning
confidence: 99%
“…Clinical data were classified according to the Total Neuropathy Scale (TNS) [18,19] using the clinical version (TNSc) [20] and the reduced version (TNSr), incorporating neurophysiological measures [21] with severity rankings of 0 (none) to 4 (very severe), as previously validated in patients with chemotherapy-induced neuropathy [21,22]. Patients' descriptions of symptoms were staged using the Neuropathy Symptom Score (NSS) into negative (subset IIA) and positive (subset IIB) sensory symptoms summed to give a composite score out of 5 [23].…”
Section: Clinical Assessment: Grading Of Neurotoxicitymentioning
confidence: 99%
“…Several trials have demonstrated that PN was more likely to appear with a high cumulative dose and that it aggravates with the highest administered doses. [47][48][49][50] A few studies have suggested a lower risk of PN with low doses. In two successive trials, Rajkumar et al reported PN in 50-80% of the patients, and this was correlated with the dose and duration of treatment.…”
Section: Incidence Severity and Risk Factors Of Thalidomide-induced mentioning
confidence: 99%